Emigration, Remittances and the Subjective Well-Being of Those Staying Behind - Artjoms Ivlevs; Milena Nikolova; Carol Lee Graham (Institute of Labor Economics (IZA), 2018)
Despite growing academic and policy interest in the subjective well-being consequences of emigration for those left behind, existing studies have focused on single origin countries or specific world regions. Our study is the first to offer a global perspective on the well-being consequences of emigration for those staying behind using several subjective well-being measures (evaluations of best possible life, positive affect, stress, and depression). Drawing upon Gallup World Poll data for 114 countries during 2009-2011, we find that both having family members abroad and receiving remittances are positively associated with evaluative well-being (evaluations of best possible life) and positive affect (measured by an index of variables related to experiencing positive feelings at a particular point in time). Our analysis provides novel results showing that remittances are particularly beneficial for evaluative well-being in less developed and more unequal contexts; in richer countries, only the out-migration of family members is positively associated with life evaluations, while remittances have no additional association. We also find that having household members abroad is linked with increased stress and depression, which are not offset by remittances. The out-migration of family members appears more traumatic in contexts where migration is less common, such as more developed countries, and specific world regions, such as Latin America and Sub-Saharan Africa, as well as among women. Relying on subjective well-being measures, which reflect both material and non-material aspects of life and are broad measures of well-being, allows us to provide additional insights and a more well-rounded picture of the possible consequences of emigration on migrant family members staying behind relative to standard outcomes employed in the literature, such as the left-behind's consumption, income or labor market responses.
Keywords: F22; F24; I3; J61; O15; 330; migration; remittances; depression; stress; Cantril ladder of life; happiness; Gallup World Poll